2021
DOI: 10.1155/2021/5588464
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Hydroalcoholic Extract of Watercress on the Levels of Protein Carbonyl, Inflammatory Markers, and Vitamin E in Chronic Hemodialysis Patients

Abstract: Introduction. Chronic kidney disorder is a main public health concern. Inflammatory processes and oxidative stress are common in end-stage renal disease patients. We aimed to evaluate the effect of the hydroalcoholic extract of watercress (WC) on the inflammatory cytokines and protein carbonyl (PCO) contents in chronic hemodialysis patients. Methods. This was a double-blind randomized clinical trial performed on 46 hemodialysis patients. The participants were randomly divided into two groups: intervention grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Previous studies confirmed that the NOE reduces inflammatory responses by inhibiting the expression of TNFα, IL-1β, and IL-6 [60,61]. According to our experiments, the administration of NOE also decreased the expression of TNF-α, IL-1β, and α-SMA similarly to the DTX treatment group in asthmatic rats.…”
Section: Evidence-based Complementary and Alternative Medicinesupporting
confidence: 86%
See 1 more Smart Citation
“…Previous studies confirmed that the NOE reduces inflammatory responses by inhibiting the expression of TNFα, IL-1β, and IL-6 [60,61]. According to our experiments, the administration of NOE also decreased the expression of TNF-α, IL-1β, and α-SMA similarly to the DTX treatment group in asthmatic rats.…”
Section: Evidence-based Complementary and Alternative Medicinesupporting
confidence: 86%
“…In one study, the antioxidant and anti-inflammatory properties of NOE were suggested to protect against bleomycin-induced pulmonary fibrosis in a rat model [ 65 ]. Accordingly, several studies have reported anti-inflammatory, antioxidant, and immune-regulating effects of the NOE [ 60 , 61 ]. This ability is due to the biological active compounds, particularly phenolics, glucosinolates, and carotenoids present in the plant, whilst much evidence approved the ability of these phytoconstituents to inhibit the production or activation of the pro-inflammatory mediators, which lead to anti-inflammatory potencies [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The plasma level of TAC was assayed by the ferric-reducing ability of plasma (FRAP) method suggested by Benzie and Strain [ 18 ]. The protein carbonyl test was performed by a spectrophotometric method [ 19 ]. The plasma MDA level was estimated using the TBA reaction assay [ 20 ].…”
Section: Methodsmentioning
confidence: 99%